(untitled) (Journal of Hama University, 2019)
- The study aimed to reveal the level of organizational loyalty of the principals of some secondary schools in Tartous city, and its relation to the degree of administrative innovation from the point of view of teachers working in these schools. - The study sample consisted of (115) teachers and teachers for the academic year (2016-2017). - The researcher used the Organizational Loyalty Scale and the Management Innovation Scale. - This study was based on descriptive analytical methodology, and the study reached a number of results, the most important of which: * The degree of organizational loyalty in the secondary schools of managers in general is medium. * The level of managerial innovation in secondary schools for managers from the teachers’ point of view was medium. In the first place, the field of "encouraging innovation" ranked second in the field of "creative ideas". There were statistically significant differences at the level of (0,05) in the degree of organizational loyalty according to gender variable, and were in favor of females. - There were statistically significant differences at the level of (0,05) in the degrees of organizational loyalty according to the variable years of experience were in favor of the least experience five years and Madon. There is a positive correlation between the level of organizational loyalty and the degree of administrative creativity at the level of significance (0,05).